Peran Religiusitas terhadap Sikap Pemaafan pada Remaja: Studi Meta-Analisis - Muttaqin, Islakhul (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
The large number of cases that occur among teenagers, such as hostility, brawls between groups and other interpersonal conflicts, indicate the low level of personal forgiveness in these teenagers. Forgiveness studies are very important to see the psychological quality of forgiveness in adolescents to reduce deviant behavior such as aggressive behavior. One factor that influences forgiveness is religiosity. The religious norms contained in forgiveness are contained in religiosity. So this research aims to review previous research regarding the relationship between religiosity and forgiveness. Through systematic literature review (SLR) research with a meta-analysis approach, this research contains 17 international and national journal articles taken from the research period from 2010 to 2024. The Meta-analysis uses the Bare-Bone Method which examining sampling and population correlation. The results of this study show that religiosity has an influence on forgiveness. The analysis found a sampling error variance of 0.0025, while the population variance was 0.047. The results of this meta-analysis support previous research on religiosity towards forgiveness. Therefore, to foster and improve forgiveness, the religiosity factor is very important to develop in interventions for adolescent forgiveness. Keywords - Forgiveness, Meta-Analysis, Religiosity.